Cache Valley Virus in Aedes japonicus japonicus Mosquitoes, Appalachian Region, United States - Fan Yang; Kevin Chan; Paul E. Marek; Philip M. Armstrong; Pengcheng Liu; Jacob E. Bova; Joshua N. Bernick; Benjamin E. McMillan; Benjamin G. Weidlich; Sally L. Paulson (Emerging Infectious Diseases, 2018)
We detected Cache Valley virus in Aedes japonicus, a widely distributed invasive mosquito species, in an Appalachian forest in the United States. The forest contained abundant white-tailed deer, a major host of the mosquito and virus. Vector competence trials indicated that Ae. j. japonicus mosquitoes can transmit this virus in this region.